Histone Deacetylase 1 Is Essential for Rod Photoreceptor Differentiation by Regulating Acetylation at Histone H3 Lysine 9 and Histone H4 Lysine 12 in the Mouse Retina - Ferreira, Renata C. [UNIFESP] (2020)
National Council for Scientific and Technological Development of Brazil